Penerapan Pembelajaran Elektronika I Berbasis Konflik Kognitif Melalui Metode Percobaan, Demonstrasi, Ceramah dan Diskusi - Kurniadi, Erawan (Jurnal Pendidikan, 2010)
The main factor owing to the low quality of learning on electronics is the lack and misconception of the prerequisite subjects. The other supporting factors are the unfamiliarity of electronic components among students, the low skill in arranging electronic components and the poor capability in applying electronic measurement device. All of the mentioned factors have become the presumptions leading to the studentsâ failure in learning. Yet, the real causes of the studentsâ failure are worth searching. This research is then attempted to set learning model through observation on studentsâ problems.This research is carried out within the framework of lesson study 2010 program funded by the dikti on the Electronics I subject, semester VA, the Physics Study Program. This research is packed under classroom action research design, with 1 lecturer model and 2 observers. The problems are overcome by cognitive conflict-based learning method posing experiments, demonstrations, preaching and discussion.The analysis results in conclusions: 1) 50% of students are not capable in using measurement device and in arranging electronic components, 2) the use of LCD infocus helps students observe the demonstration, even from re4atively far places, 3) discussion can encourage students to make cognitive conflicts to reach the most proper concepts, 4) preaching method given in more than 30 minutes makes students get bored, which is then resolved by combination of 10 minutes preaching and 10 minutes discussion respectively.Key words: cognitive conflict, experiments, demonstration, preaching, discussion.